FACI Is a Novel CREB-H–Induced Protein That Inhibits Intestinal Lipid Absorption and Reverses Diet-Induced ObesitySummary - Yun Cheng (Cellular and Molecular Gastroenterology and Hepatology, 2022)
Background & Aims: CREB-H is a key liver-enriched transcription factor governing lipid metabolism. Additional targets of CREB-H remain to be identified and characterized. Here, we identified a novel fasting- and CREB-H–induced (FACI) protein that inhibits intestinal lipid absorption and alleviates diet-induced obesity in mice. Methods: FACI was identified by reanalysis of existing transcriptomic data. Faci-/- mice were generated by clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated 9 (Cas9)-mediated genome engineering. RNA sequencing was performed to identify differentially expressed genes in Faci-/- mice. Lipid accumulation in the villi was assessed by triglyceride measurement and Oil red O staining. In vitro fatty acid uptake assay was performed to verify in vivo findings. Results: FACI expression was enriched in liver and intestine. FACI is a phospholipid-binding protein that localizes to plasma membrane and recycling endosomes. Hepatic transcription of Faci was regulated by not only CREB-H, but also nutrient-responsive transcription factors sterol regulatory element-binding protein 1 (SREBP1), hepatocyte nuclear factor 4α (HNF4α), peroxisome proliferator-activated receptor γ coactivator-1α (PGC1α), and CREB, as well as fasting-related cyclic adenosine monophosphate (cAMP) signaling. Genetic knockout of Faci in mice showed an increase in intestinal fat absorption. In accordance with this, Faci deficiency aggravated high-fat diet–induced obesity, hyperlipidemia, steatosis, and other obesity-related metabolic dysfunction in mice. Conclusions: FACI is a novel CREB-H–induced protein. Genetic disruption of Faci in mice showed its inhibitory effect on fat absorption and obesity. Our findings shed light on a new target of CREB-H implicated in lipid homeostasis.